Nega in higiena tekstilij: Dnevnik laboratorijskih vaj - Kurečič, Manja; Neral, Branko (University of Maribor Press, 2021)
Textile Care and Hygiene: Laboratory Instructions. Laboratory work instructions "Textile Care and Hygiene, Laboratory Instructions" covers the area of evaluating the effectiveness of the removal of impurities and the disinfectant effect of the washing process and is intended to help students throughout the laboratory work. Textile care and hygiene is an important part of our lives that we deal with on a daily basis in our households and industrial laundries. The main task of laundries is to return dirty, contaminated textiles to a clean, fresh and disinfected state without excessive damage to textiles, for further use. When evaluating the effects of disinfection in textile washing process, we determine the number and type of surviving microorganisms and fungi under certain incubation conditions. Using textile bioindicators, we determine the efficiency of removing impurities and the disinfecting effect of the cleaning and washing process.